Anatomy of Human Sensory Cortices Reflects Inter-Individual Variability in Time Estimation - Gilaie-Dotan, Sharon; Kanai, Ryota; Rees, Geraint (Frontiers in Integrative Neuroscience, 2011)
The ability to estimate duration is essential to human behavior, yet people vary greatly in their ability to estimate time and the brain structures mediating this inter-individual variability remain poorly understood. Here, we showed that inter-individual variability in duration estimation was highly correlated across visual and auditory modalities but depended on the scale of temporal duration. We further examined whether this inter-individual variability in estimating durations of different supra-second time scales (2s or 12s) was reflected in variability in human brain anatomy. We found that the gray matter volume in both the right posterior lateral sulcus encompassing primary auditory and secondary somatosensory cortex, plus parahippocampal gyrus strongly predicted an individual’s ability to discriminate longer durations of 12s (but not shorter ones of 2s) regardless of whether they were presented in auditory or visual modalities. Our findings suggest that these brain areas may play a common role in modality-independent time discrimination. We propose that an individual’s ability to discriminate longer durations is linked to self-initiated rhythm maintenance mechanisms relying on the neural structure of these modality specific sensory and parahippocampal cortices.